Explaining the Correlates of Child Mortality and Under-5 Survival in Nigeria - Molelekoa, Thonaeng Charity; Oyekale, Abayomi Samuel (Jurnal Ilmu Kesehatan dan Kesehatan, 2024)
Background: Survival of children under-5 is among the foremost public health concerns that has been pursued in the Sustainable Development Goals (SDGs). A proper understanding of the correlates of child survival is of paramount relevance to health policy formulation and development of interventions to promote child's health outcomes. This study therefore analysed the determinants of the number of recorded child mortality and survival in Nigeria. Subject and Methods: The data were the Malaria Indicator Survey (MIS) that were collected in Nigeria in 2021. The samples were drawn with multi-stage sampling method following the 2023 Population and Housing Census sampling frame. A total of 14185 housing units were randomly selected of which 13887 were occupied and 13727 were successfully interviewed. In each household, all women belonging to the reproductive ages of 15-49 years were interviewed. A total of 14647 women were eligible, of which 14476 were successfully interviewed (Demographic and Health Survey (DHS), 2021). The data were analyzed using the Negative Binomial regression and logistic regression models. Results: The logs of the number of dead children were significantly higher (p<0.05) for mothers from North West and North East Nigeria, while children from these regions also had a significantly lower probability of surviving. The mothers from urban areas had significantly lower log of dead children while urban children had significantly higher probability of surviving. Mothers with secondary and tertiary education had significantly lower log of dead children, while birth in the past five years and total children born reduced child’s survival. Twin children also had a significantly lower probability of surviving while mother’s maturity promoted child’s survival. Conclusion: Promotion of child survival in Nigeria requires a concerted effort that disaggregates interventions across Nigerian zones with preferences for those in the north and rural dwellers. In addition, there is the need to promote interventions to assist women with multiple births, promote girl child education and discourage teenage pregnancies.